Activation and clustering of a Plasmodium falciparum var gene are affected by subtelomeric sequences. (9th December 2016) - Duffy, Michael F.; Tang, Jingyi; Sumardy, Fransisca; Nguyen, Hanh H. T.; Selvarajah, Shamista A.; Josling, Gabrielle A.; Day, Karen P.; Petter, Michaela; Brown, Graham V.
Abstract : Nuclear architecture may regulate Plasmodium falciparum var genes. We show that subtelomeric sequences cis to a var gene affect both its association with telomeric clusters and its propensity to be activated. However, the var gene can still be transcribed inside or outside of the telomeric cluster. The active var gene promoter carries acetylated H3K27 which could confer epigenetic memory. Abstract : The Plasmodium falciparum var multigene family encodes the cytoadhesive, variant antigen PfEMP1. P. falciparum antigenic variation and cytoadhesion specificity are controlled by epigenetic switching between the single, or few, simultaneously expressed var genes. Most var genes are maintained in perinuclear clusters of heterochromatic telomeres. The active var gene(s) occupy a single, perinuclear var expression site. It is unresolved whether the var expression site forms in situ at a telomeric cluster or whether it is an extant compartment to which single chromosomes travel, thus controlling var switching. Here we show that transcription of a var gene did not require decreased colocalisation with clusters of telomeres, supporting var expression site formation in situ . However following recombination within adjacent subtelomeric sequences, the same var gene was persistently activated and did colocalise less with telomeric clusters. Thus, participation in stable, heterochromatic, telomere clusters and var switching are independent but are both affected by subtelomeric sequences. The var expression site colocalised with the euchromatic mark H3K27ac to a greater extent than it did with heterochromatic H3K9me3. H3K27ac was enriched within the active var gene promoter even when the var gene was transiently repressed in mature parasites and thus H3K27ac may contribute to var gene epigenetic memory.